ACCOUNTING PRACTICES OF LISTED COMPANIES IN THE ENGINEERING SECTOR OF BANGLADESH - Ayon, Abdul Khalak; Sayeem, Md. Muhtashim Rahman; Masum, Mofijul Hoq (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2025)
Accounting practices are very crucial to ensure the reliability and reporting of financial issues all over the world. This study examines the accounting practices of the Engineering sector listed on the Dhaka Stock Exchange (DSE). This study is based on 37 companies’ annual reports out of a total population of 41 companies. This empirical study considers five years of annual reports from 2020 to 2024. Finally, a purposive sample of 185 annual reports is explored to achieve the study's objectives. By analysing these annual reports, this study explores some key accounting practices used by Engineering sector companies in an emerging economy context. This study finds that most companies follow the same accounting practices for their company. It is found that the reporting was done by the following International Accounting Standards and International Financial Reporting Standards. The findings of the study will provide insights to the regulatory bodies, academicians, and business consultants about the accounting tools most common in an emerging economy. Moreover, the policymaker may shape future accounting policies focusing on the findings of the study.